Identity Construction of the Main Character in the Novel “Mashatun” by Hani As-Salmi: An Analysis of Gramsci's Hegemony Theory - Farikhatul Khusniyah; Arief Rahman Hakim (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
This research aims to determine how the forms of Israeli power hegemony psychologically impact the Palestinian people, as represented through the main character in Hani As-Salmi's novel "Mashatun." Hegemony and its impacts cause the construction of a person's identity, influenced by oneself and their social life. This research employs a descriptive qualitative method. The primary data source is the narration and dialogue in Hani As-Salmi's novel "Mashatun." Meanwhile, secondary data sources consist of books and articles relevant to the researcher's objectives and topic. The data collection technique in this research is the note-taking technique, with data analysis using Miles and Huberman's method, which comprises three analysis techniques: data reduction, data presentation, and conclusion drawing. The results of this study indicate three forms of power hegemony, namely authoritarian, capitalism, and consensus, totaling 6 data points. Additionally, the impact of power hegemony on the main character is shown in 9 data points, representing forms of in-group and out-group attitudes or personalities. Furthermore, 4 data points demonstrate character changes in the main character. Based on the research findings, it can be concluded that the forms of Zionist Israeli power hegemony create a psychological impact on the main character. Consequently, power hegemony becomes one of the factors in the formation of the main character's personality or identity construction, built from a series of events or experiences.